GateOS : a minimalist windowing environment and operating system for FPGAs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Systems Engineering at Massey University, Palmerston North, New Zealand - Buhler, Andreas (Massey University, 2007)
In order to debug and tune stand-alone FPGA image processing configurations, it is necessary for a developer to also create the required debug tools and to implement them on the FPGA. This process takes both time and effort that could be better spent on improving the image processing algorithms. The Gate Array Terminal Operating System (GateOS) is proposed to relieve the developer of the need to construct many of these debugging tools. In GateOS we separate the image processing algorithms from the rest of the operating system. GateOS is presented to the developer as a Handel-C library, which can be customised at compile-time, to facilitate the creation of windows and widgets. Several types of widgets are described that can manipulate the parameters of image processing algorithms and enable the end-user to dynamically rearrange the position of a window on the VDU. An end user is able to interact with GateOS with both a keyboard and a mouse.
Keywords: Field Programmable Gate Array; Image processing; Operating system; Windows (Computers); Widgets; Fields of Research::290000 Engineering and Technology::291600 Computer Software